Pelatihan dan Sosialisasi Mempertahankan Produksi dan Penjualan Produk UMKM dengan Strategi Pemasaran Melalui Media Sosial Dimasa Pendemi COVID-19 - Mujilahwati, Siti; Rakhmawati, Eka; Salim, Kevin Aringgi; Adawiyah, Robiatul (Universitas Nusantara PGRI Kediri, 2022)
During the Covid-19 Pandemic at this time, Micro, Small, and Medium Enterprises (MSMEs) in the villages of Soko, Panceng, Sawo, and Pucuk have to think hard about how the products they produce can continue to be known by buyers from outside their area. Before the pandemic, they were able to sell their products from the hands of mobile salesmen who were usually able to sell products from warungs to warungs and house to house. However, during a pandemic like this, it will be very risky if salespeople have to keep going around peddling the products they sell. From there, we have provided solutions for MSME players to be able to promote their products through advertisements on their respective social media. With the promotion on social media, buyers can contact the seller directly through the contact person who has been confirmed in the advertising information. With that, the sales will change their position to become couriers between orders, which have different work procedures. Sales can be that the products they sell don't run out and the risk of being exposed to Covid-19 is everywhere. Meanwhile, with the online promotion strategy, sales become couriers according to incoming orders and it is clear that the products they deliver are orders from buyers. From the strategy that has been implemented, the actors of the village umkm are still running, marketing is expanding and sales are still working as delivery couriers.